Expression of lipolytic genes in adipose tissue is differentially regulated during multiple phases of dietary intervention in obese women - Koppo, K; Valle, C; Šiklová, Michaela; Krauzová, Eva; Glisezinski, I. de; Voorde, J. van de; Langin, Dominique; Štich, Vladimír (Physiological research, 2013)
The aim of this study was to investigate the time-course of the expression of key lipolysis-regulating genes in the subcutaneous adipose tissue (SCAT) during different phases of a 6-month dietary intervention. Fifteen obese women (BMI 34.7+/-1.0 kg.m(-2)) underwent a 6-month dietary intervention consisting of 1 month very low calorie diet (VLCD), followed by 2 months low calorie diet (LCD) and 3 months weight maintenance diet (WM). At each phase of the dietary intervention, a needle microbiopsy of the abdominal SCAT was obtained to evaluate mRNA expression of key lipolysis-regulating genes and a hyperinsulinemic euglycemic clamp (HEC) was performed. Dietary intervention induced a body weight reduction of 9.8 % and an improvement of insulin sensitivity as assessed by a HEC. Compared to pre-diet levels, mRNA levels of the adrenergic beta(2)-receptor in SCAT were higher at the end of VLCD and not different at the end of LCD and WM. In contrast, the expression of the adrenergic alpha(2)-receptor was lower at the end of VLCD and LCD compared to the pre-diet levels and did not differ at WM. Adipose triglyceride lipase and hormone-sensitive lipase levels were lower than the pre-diet levels at the end of LCD only, while phosphodiesterase-3B and the insulin receptor levels did not change throughout the dietary intervention. The results suggest that the regulation pattern of the genes that are involved in the control of lipolysis is different at the respective phases of the dietary intervention and depends on the duration of the diet and the status of energy balance.
Keywords: RNA, Messenger; Humans; Treatment Outcome; Energy Metabolism; Caloric Restriction; Weight Loss; Subcutaneous Fat, Abdominal; podkožní břišní tuk; energetický metabolismus; lidé; messenger RNA; Obesity; hmotnostní úbytek; výsledek terapie; Female; časové faktory; Lipolysis; Time Factors; kalorická restrikce; regulace genové exprese; Gene Expression Regulation; ženské pohlaví; obezita; lipolýza